The impact of primary healthcare in reducing inequalities in child health outcomes, Bogotá – Colombia: an ecological analysis - Mosquera, Paola A; Hernández, Jinneth; Vega, Román; Martínez, Jorge; Labonte, Ronald; Sanders, David; Sebastián, Miguel S (Université d'Ottawa | University of Ottawa, 2012)
Abstract Background Colombia is one of the countries with the widest levels of socioeconomic and health inequalities. Bogotá, its capital, faces serious problems of poverty, social disparities and access to health services. A Primary Health Care (PHC) strategy was implemented in 2004 to improve health care and to address the social determinants of such inequalities. This study aimed to evaluate the contribution of the PHC strategy to reducing inequalities in child health outcomes in Bogotá. Methods An ecological analysis with localities as the unit of analysis was carried out. The variable used to capture the socioeconomic status and living standards was the Quality of Life Index (QLI). Concentration curves and concentration indices for four child health outcomes (infant mortality rate (IMR), under-5 mortality rate, prevalence of acute malnutrition in children under-5, and vaccination coverage for diphtheria, pertussis and tetanus) were calculated to measure socioeconomic inequality. Two periods were used to describe possible changes in the magnitude of the inequalities related with the PHC implementation (2003 year before - 2007 year after implementation). The contribution of the PHC intervention was computed by a decomposition analysis carried out on data from 2007. Results In both 2003 and 2007, concentration curves and indexes of IMR, under-5 mortality rate and acute malnutrition showed inequalities to the disadvantage of localities with lower QLI. Diphtheria, pertussis and tetanus (DPT) vaccinations were more prevalent among localities with higher QLI in 2003 but were higher in localities with lower QLI in 2007. The variation of the concentration index between 2003 and 2007 indicated reductions in inequality for all of the indicators in the period after the PHC implementation. In 2007, PHC was associated with a reduction in the effect of the inequality that affected disadvantaged localities in under-5 mortality (24%), IMR (19%) and acute malnutrition (7%). PHC also contributed approximately 20% to inequality in DPT coverage, favoring the poorer localities. Conclusion The PHC strategy developed in Bogotá appears to be contributing to reductions of the inequality associated with socioeconomic and living conditions in child health outcomes.